Some Geometric Properties of the Domain of the Double Sequential Band Matrix in the Sequence Space - Havva Nergiz; Feyzi Başar (Abstract and Applied Analysis)
The sequence space was introduced by Maddox (1967). Quite recently, the sequence space of nonabsolute type has been introduced and studied which is the domain of the double sequential band matrix in the sequence space by Nergiz and Başar (2012). The main purpose of this paper is to investigate the geometric properties of the space , like rotundity and Kadec-Klee and the uniform Opial properties. The last section of the paper is devoted to the conclusion.